2020
DOI: 10.4028/www.scientific.net/jbbbe.48.85
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of <i>Binahong </i>Leaves Extract Gel on Wound Healing of the Palatal Mucosa

Abstract: Wound healing is a complex and integrated process that requires the collective roles of various cells and tissues of the palatal mucosa. During the proliferation phase, the sum of fibroblasts increases in response to damaged oral tissues. Thus, the number of fibroblast cells in the palatal mucosa is a substantial indicator of wound healing. Binahong leaves possess the potential to accelerate wound healing by stimulating fibroblast proliferation. This study aimed to formulate and evaluate the effect of Binahong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 20 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…The concentration of the Binahong leaf extract gel in this study was chosen based on a previous research by Hanafiah et al , which examined the effects of Binahong leaf extract gel on the healing of palatal mucosal wounds. 30 Among the various Binahong leaf extract gel concentrations in the research, 3% Binahong leaf extract gel showed the best affinity in increasing fibroblast proliferation. 30 In this study, the RSV in every treatment group decreased over time and the Binahong group showed a lower RSV in comparison with the other treatment groups on the 7 th and the 14 th day (p < 0.05).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The concentration of the Binahong leaf extract gel in this study was chosen based on a previous research by Hanafiah et al , which examined the effects of Binahong leaf extract gel on the healing of palatal mucosal wounds. 30 Among the various Binahong leaf extract gel concentrations in the research, 3% Binahong leaf extract gel showed the best affinity in increasing fibroblast proliferation. 30 In this study, the RSV in every treatment group decreased over time and the Binahong group showed a lower RSV in comparison with the other treatment groups on the 7 th and the 14 th day (p < 0.05).…”
Section: Discussionmentioning
confidence: 88%
“… 30 Among the various Binahong leaf extract gel concentrations in the research, 3% Binahong leaf extract gel showed the best affinity in increasing fibroblast proliferation. 30 In this study, the RSV in every treatment group decreased over time and the Binahong group showed a lower RSV in comparison with the other treatment groups on the 7 th and the 14 th day (p < 0.05). A lower RSV implied a decrease in socket wound size, so it can be assumed that the Binahong group showed a better affinity in accelerating wound closure compared to the positive and negative control groups.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Besides, injury in the palatal site is undeniable which can be caused by trauma, defect, or surgical procedures [6,7]. Palatal wound usually heals in 2-3 w and is more likely to develop scar tissue after healing [8]. Wound healing is a complicated physiological process which involves numbers of cells and chemical mediators (such as cytokines, chemokines, and growth factors) as described in many studies [9,10].…”
Section: Introductionmentioning
confidence: 99%